HMIP prisoner survey: adults in England and Wales, 2000-2025 (UK Data Service, 2025)
The HMIP (His Majesty's Inspectorate of Prisons) Prisoner Surveys (also formerly known as Detainee Surveys) are part of the Inspectorate's duties to inspect prisons. Surveys of prisoners have been carried out systematically since 2000 at institutions being inspected, to gain important insight into detainees' experiences of offender management whilst in custody. Prisoners are issued with the survey questionnaire to return to the HMIP team, which processes the data to inform inspections of individual institutions and the HMIP annual reports. The survey is grouped into topics/themes of questions with response categories, as well as providing space for prisoners to add additional comments (such text comments are not included in these datasets). Two versions of the HMIP Prisoner Survey are held at UKDS: an End User Licence (EUL) version (SN 9161) that is subject to registration and standard access conditions, and a more detailed Special Licence (SL) version (SN 9068), which has additional access restrictions. The document 'end_user_licence_group_changes', available with the EUL version, SN 9161, details the differences between the two versions. Users should obtain the EUL version first to see whether it is suitable for their needs before considering making an application for access to the SL version. For the third edition (August 2025), data and documentation for 2024/25 were added to the study.